2021
DOI: 10.1002/adfm.202107538
|View full text |Cite
|
Sign up to set email alerts
|

A Stiff yet Rapidly Self‐Healable Elastomer in Harsh Aqueous Environments

Abstract: Rapid underwater self-healing elastomers with high mechanical strength at ambient temperature are highly desirable for dangerous underwater operations. However, current room temperature self-healing materials have shortcomings, such as low healing strength (below megapascal), long healing time (hours), and decay of healing functions in harsh environments (salty, acidic, and basic solutions), limiting their practical applications. Herein, it is introduced water-stable Debye forces and high-density nano-sized ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 51 publications
1
44
0
Order By: Relevance
“…There are also dipole–dipole and ion–dipole interactions among the cations, carbonyls, and ether groups. The ICE, therefore, would form a cross-linked structure with π–π aggregates and could not be fully dissolved in organic solvents. However, it should also be noted that the slightly cross-linked feature could be in part due to a chain transfer reaction during the free radical polymerization in the presence of ethylene glycol-based monomers …”
Section: Resultsmentioning
confidence: 99%
“…There are also dipole–dipole and ion–dipole interactions among the cations, carbonyls, and ether groups. The ICE, therefore, would form a cross-linked structure with π–π aggregates and could not be fully dissolved in organic solvents. However, it should also be noted that the slightly cross-linked feature could be in part due to a chain transfer reaction during the free radical polymerization in the presence of ethylene glycol-based monomers …”
Section: Resultsmentioning
confidence: 99%
“…Our composite shows an excellent η of 100.04% (Figure b). Compared to self-healing materials on the basis of dynamic supramolecular interactions, the PAA–GAs@LMPs composite achieves higher mechanical strength and toughness with satisfactory self-healing efficiency at room temperature (Figure c, Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Noncovalent interactions such as hydrogen bonding, electrostatic interactions, and π–π interactions , were widely applied to enhance the interfacial strength among phases of blends. However, forming these special interactions usually requires complicated chemical synthesis and processing steps to introduce specific functional groups such as hydroxyl groups into polymer chains. , Recently, strong interchain van der Waals interaction (VDW) has emerged as a promising tool to fabricate novel polymer materials with excellent performances. Using the key-and-lock interchain junction mechanism formed by favorable interchain van der Waals forces, Urban et al reported the commodity copolymers such as PMMA/ n -butyl acrylate [P­(MMA/ n BA)], and their derivatives exhibited interesting self-healing performance. Compared to the supramolecular interaction, the strong van der Waals interaction such as dipolar interaction was more easily fulfilled in the commodity polymer without complicated chemical and physical alterations. …”
Section: Introductionmentioning
confidence: 99%